Impact of a Gender-Transformative HIV and Antiviolence Program on Gender Ideologies and Masculinities in Two Rural, South African Communities. (June 2013) - Dworkin, Shari L.; Hatcher, Abigail M.; Colvin, Chris; Peacock, Dean
"One Man Can" (OMC) is a rights-based gender equality and health program implemented by Sonke Gender Justice Network (Sonke) in South Africa. The program seeks to reduce the spread and impact of HIV and AIDS and reduce violence against women and men. To understand how OMC workshops impact masculinities, gender norms, and perceptions of women's rights, an academic/non-governmental organization (NGO) partnership was carried out with the University of Cape Town, the University of California at San Francisco, and Sonke. Sixty qualitative, in-depth interviews were carried out with men who had completed OMC workshops and who were recruited from Sonke's partner organizations that were focused on gender and/or health-related services. Men were recruited who were over age 18 and who participated in OMC workshops in Limpopo and Eastern Cape Provinces, South Africa. Results reveal how men reconfigured notions of hegemonic masculinity both in terms of beliefs and practices in relationships, households, and in terms of women's rights. In the conclusions, we consider the ways in which the OMC program extends public health research focused on masculinities, violence, and HIV/AIDS. We then critically assess the ways in which health researchers and practitioners can bolster men's engagement within programs focused on gender equality and health.